2018
DOI: 10.1038/s41598-018-28326-9
|View full text |Cite
|
Sign up to set email alerts
|

Widespread distribution of prophage-encoded virulence factors in marine Vibrio communities

Abstract: Prophages are known to encode important virulence factors in the human pathogen Vibrio cholerae. However, little is known about the occurrence and composition of prophage-encoded traits in environmental vibrios. A database of 5,674 prophage-like elements constructed from 1,874 Vibrio genome sequences, covering sixty-four species, revealed that prophage-like elements encoding possible properties such as virulence and antibiotic resistance are widely distributed among environmental vibrios, including strains cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
86
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(99 citation statements)
references
References 45 publications
(68 reference statements)
3
86
2
Order By: Relevance
“…Many vibriophages contain virulence genes responsible for severe gastro-intestinal diseases (47, 48). For instance, almost 80% of clinical V. parahaemolyticus strains contain filamentous phages, encoding the zona occludens toxin (Zot) (22). Also, non-human pathogens, such as V. coralliilyticus and V. anguillarum contain prophage-like elements encoding Zot, suggesting frequent horizontal gene transfer (HGT) of Zot via prophages among vibrios (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many vibriophages contain virulence genes responsible for severe gastro-intestinal diseases (47, 48). For instance, almost 80% of clinical V. parahaemolyticus strains contain filamentous phages, encoding the zona occludens toxin (Zot) (22). Also, non-human pathogens, such as V. coralliilyticus and V. anguillarum contain prophage-like elements encoding Zot, suggesting frequent horizontal gene transfer (HGT) of Zot via prophages among vibrios (11).…”
Section: Discussionmentioning
confidence: 99%
“…We predict, that also filamentous phages isolated from environmental vibrios, may contain virulence factors responsible for disease outbreaks in marine eukaryotes. Indeed, a closer look at more than 1,800 Vibrio genome sequences, covering 64 species revealed that 45% harboured filamentous phages which encoded Zot-like proteins (22). Even though a detailed characterization of these phages is missing, this study suggests that also filamentous vibriophages of non-human pathogens contain virulence genes in (22).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Castillo et al. () revealed that the prophage‐like elements encoding possible virulence and antibiotic resistance are widely distributed among the 64 species of environmental vibrios, including those classified as nonpathogenic.…”
Section: Transmission and Virulence Factors Influencing Vibriosismentioning
confidence: 97%
“…; Castillo et al. ), while integration of genomic and phenotypic features enlightens the molecular evolution of the pathogenic Vibrio spp. (Castillo et al.…”
Section: Potential Control and Prevention Measures Against Vibriosismentioning
confidence: 99%
“…Recent assessment of prophages in diverse marine populations of Vibrio spp. suggests that filamentous prophages are numerous and widespread and play comprehensive roles in evolution through shaping niche adaptation and emergence of novel pathogenic strains emerging from environmental Vibrio communities . Recently, a prophage with a similar genomic arrangement to CTXφ has been described in the human pathogen Acinetobacter baylyi (and A. baumannii ) genome, though no homologous CTX toxin is present .…”
Section: Escherichia Coli Ff: the Archetypal Filamentous Phagementioning
confidence: 99%